Digital Transformation in Entrepreneurship Education: A Systematic Literature Review on Technology Utilization and Student Learning Outcomes - Kusumaningtyas, Ary Wijayati; Heryatno, Roni; Prakosa, Gatot Hendro; Budi, Satria (Dinasti Publisher, 2025)
Digital transformation has fundamentally changed the way entrepreneurship is taught in higher education institutions. Educational institutions now employ various technological platforms to enrich the learning process. However, a comprehensive understanding of the impact of various digital media and technologies on entrepreneurship education outcomes remains to be deepened. This study conducts a systematic review to integrate various studies on the use of digital media and technologies in entrepreneurship learning, and analyzes their impact on learning outcomes, active participation, and students' entrepreneurial intentions. Following the PRISMA protocol, a systematic search was conducted through Web of Science, Scopus, ERIC, and IEEE Xplore databases for the period 2015-2024. The search was performed using keyword combinations related to digital technology, entrepreneurship learning, and higher education contexts. From the search results, 38 studies that met the criteria were analyzed using thematic synthesis methods. Three dominant digital technology classifications were identified: (1) Social Media (Facebook, LinkedIn, Instagram), (2) Digital Learning Platforms (MOOCs, Moodle, specialized systems), and (3) Mobile-Based Learning. Results show that social media use significantly enhances students' networking abilities and participation. Mobile learning provides access convenience and flexibility. Digital platforms have a positive impact on entrepreneurship concept mastery, mindset formation, and entrepreneurial behavioral intentions, especially in regions with high digital penetration. Digital transformation in entrepreneurship learning yields encouraging results in improving participation and learning effectiveness. Successful implementation requires careful planning regarding teaching methods, technological infrastructure, and local cultural aspects. Future studies should focus on longitudinal research to assess the impact of digital learning on actual entrepreneurship practices.